Keberadaan Ritual Oke Saki pada Masyarakat Beo Kalo, Desa Lentang, Kecamatan Lelak Kabupaten Manggarai - Maria Calin De Putri; Ida Bagus Oka Wedasantara; Aliffiati Aliffiati (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2025)
Oke saki believed by the community Live If is one of the efforts or ways of the local community to erase sins or remove all mistakes made by ancestors as an effort to prevent bad luck or disaster for the next generation. RitualOke Sakicarried out from generation to generation based on local beliefs, especially community beliefsLiveRegarding supernatural powers that are still practiced today, even though currently the majority of them have embraced Catholicism. The results of this study reveal that the background of societyLiveIf you are still carrying out the ritualOke Sakinamely, the belief in legends or curses, to avoid disasters, and efforts to overcome life's problems. So that the ritualOke SakiThis is still carried out today by the communityLiveIf. RitualOke Sakiplays an important role in the survival of the local community because by carrying out ritualsOke SakiThis local community can overcome the disasters that happen to their descendants, because it is believed that if the ritual is carried outOke SakiIf this is not carried out, it will have a bad impact on their generations up to seven generations. Ritual Oke Saki which is part of the community's traditionLiveKalo is a ritual related to the elimination of sins or mistakes made by the ancestors of the local community which resulted in their descendants experiencing and bearing the sins they committed.